Pendidikan Karakter dalam Al-Qur’an Surah Al-Qalam Ayat 4 dan Surah Al-Baqarah Ayat 177 - Eka Susanti; Mahyuddin Barni (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Character education is a crucial aspect in shaping individuals with noble morals and behavior aligned with higher values. The Qur’an, as the guiding principle for Muslims, contains fundamental principles of character education. This study examines Surah Al-Qalam, verse 4, which emphasizes the importance of integrity, patience, and steadfastness in facing trials, as well as Surah Al-Baqarah, verse 177, which highlights faith, honesty, social care, and righteous deeds as manifestations of true virtue. The analysis employs a thematic tafsir approach to explore the character values contained in both verses. The findings suggest that character education in the Qur’an encompasses not only internal development, through the cultivation of faith and morality, but also external aspects, including concern for others, justice, and social righteousness. These findings suggest that integrating Qur’anic values into character education can shape individuals who are balanced in spirituality, morality, and social responsibility.